2016
DOI: 10.1177/1094670516680033
|View full text |Cite
|
Sign up to set email alerts
|

The MINDS Method

Abstract: As technology innovation rapidly changes service experiences, service designers need to leverage technology and orchestrate complex service systems to create innovative services while enabling seamless customer experiences. Service design builds upon contributions from multiple fields, including management, information technology, and interaction design. Still, more integration to leverage the role of technology for service innovation is needed. This article integrates these two service design perspectives, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(42 citation statements)
references
References 66 publications
0
34
0
1
Order By: Relevance
“…This contrasts one of the key outcomes of the meta-synthesis, which relates to the importance of reflexivity and procedural knowledge with respect to experience design processes. The combination of Grenha Teixeira et al (2017) and Patrício et al (2011) forms a possible exception here, as they explicitly mention a systematic approach to developing their respective design processes and their structural validity based on the Analysis-Synthesis bridge model (Dubberly et al, 2008). Moreover, the former of those papers can be seen as an adapted version/application of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts one of the key outcomes of the meta-synthesis, which relates to the importance of reflexivity and procedural knowledge with respect to experience design processes. The combination of Grenha Teixeira et al (2017) and Patrício et al (2011) forms a possible exception here, as they explicitly mention a systematic approach to developing their respective design processes and their structural validity based on the Analysis-Synthesis bridge model (Dubberly et al, 2008). Moreover, the former of those papers can be seen as an adapted version/application of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the effects of a single element without considering its interactions with others is insufficient. Clients’ experience is holistic, encompassing every contact with the healthscape [57]. This study examined the combination of all design elements of the healthscape, including the physical environment, service delivery process, and social interaction factors.…”
Section: Discussionmentioning
confidence: 99%
“…Lin and Mattila [53] suggested that, following the concept of Gestalt, customers generally receive a variety of stimuli from the restaurant servicescape and view every encounter holistically, considering multiple aspects in their experience evaluation. Customer experience is holistic, encompassing every contact with a firm, so all service encounters need to be seamlessly orchestrated [57]. Accordingly, this study assumed clients to consider multiple atmospheric cues, tangible elements, and services of the healthscape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at present, the knowledge system and ability system of the specialty and talent training need to be adjusted and updated. In terms of talent training objectives, talent training programs, curriculums, and teaching evaluations, it is not only necessary to emphasize the basic, personalized, practical, integrated, and service-oriented cultivation but also to strengthen the guidance of students' innovation consciousness, social responsibility, industry-university-research and multi-dimensional professional evaluation (Grenha Teixeira et al, 2017), which can better cope with the new needs of international service design talent.…”
Section: Introductionmentioning
confidence: 99%